Problematic eating behaviors and psychopathology in patients undergoing bariatric surgery: The mediating role of loss of control eating - Conceição, Eva Martins (2018)
ObjectiveThis study compares different problematic eating behaviors (PEBs; objective [OBE]/subjective [SBE] binge-eating and compulsive [CG]/noncompulsive [NCG] grazing) in relation to the severity of loss of control (LOC) and psychopathology. We also investigate LOC as a mediator between PEBs and psychopathology.MethodThis cross-sectional study assessed a group of patients before bariatric surgery (n=163), and a group of bariatric patients 12 months or more after surgery (n=131). Face-to-face assessment: Eating Disorders Examination for binge-eating episodes; Rep(eat) for grazing. LOC was measured by five questions answered in a 5-point Likert scale. Self-report measures: disordered eating, grazing, negative urgency, depression, anxiety, and stress.ResultsOBEs were reported by 26(8.8%), SBE by 29(9.8%), CG by 35(11.9%), and NCG by 36(12.2%) of patients. The different PEBs differed significantly in the severity of LOC (F(3,120)= 25.81, p<.001). Patients reporting OBEs scored higher and patients with NCG scored lower in most measures than patients with other PEBs. Patients with any PEBs scored higher in all self-report measures than those not reporting any PEBs, with statistical significance reached for uncontrolled eating (F(4,288)= 20.21, p<.001), emotional eating (F(4,288)= 23.10, p<.001), repetitive eating F(4,288)= 18.34, p<.001), and compulsive grazing (F(4,288)= 27.14, p<.001). LOC was found to be a full mediator between PEBs and psychopathology.DiscussionThere is no evidence that the different PEBs differ in the psychopathology severity, independently of the experience of LOC eating during the eating episodes. We show evidence for the conceptualization of different PEB, including grazing, on a continuous scale of LOC and psychopathology.